STIMA DE SINE - ELEMENT IMPORTANT ÎN PROIECTAREA CARIEREI - Carolina PLATON; Viorica CHETRARI (Moldova State University, 2015)
Savanţii susţin că doar o persoană cu stimă de sine înaltă are şanse să-şi dea seama de propriul potenţial. În procesul de orientare în carieră stima de sine va ajuta persoana să ia decizii corecte, să se autoevalueze şi să acţioneze în sensul aspiraţiilor sale. SELF-ESTEEM - AN IMPORTANT ELEMENT IN THE CAREER PLANNING PROCESS The scientists support the idea about the awakening that is happening throughout the world to the fact that a human being cannot realize his potential without a healthy self-esteem. A high self-esteem will help a person to make decisions, self-assessment and to act according to his aspirations in the career planning process.